2022
DOI: 10.2147/opth.s348364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Phacoemulsification Surgery in Trabeculectomy Surgery Outcomes

Abstract: To evaluate whether previous clear-cornea phacoemulsification surgery affects the surgical outcomes of trabeculectomy in open-angle glaucoma (OAG). Methods: We performed a retrospective cohort study, which included 82 patients with OAG that underwent trabeculectomy between January 1, 2010, and December 31, 2017. The primary outcome was the probability of surgical failure. Failure was defined as IOP >21 mmHg or reduced <20% from baseline, IOP ≤5 mmHg in three consecutive visits, need for further glaucoma surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…The current study results differ than that reported by Torres-Costa et al [18] who could not find significant difference between phakic and pseudophakic eyes, regarding failure rate after trabeculectomy for OAG. Another study by Supawavej et al [7] retrospectively evaluated the success rate of trabeculectomy in 39 phakic and 39 pseudophakic eyes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The current study results differ than that reported by Torres-Costa et al [18] who could not find significant difference between phakic and pseudophakic eyes, regarding failure rate after trabeculectomy for OAG. Another study by Supawavej et al [7] retrospectively evaluated the success rate of trabeculectomy in 39 phakic and 39 pseudophakic eyes.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, choroidal detachment reported in excess in pseudophakic eyes, but with insignificant difference than phakic group. These results are in line to that reported by Torres-Costa et al [18] who reported comparable results, where choroidal detachment was reported among 20.8% and 10.3% of pseudophakic and phakic eyes, respectively. Takihara et al [8] also observed more frequency choroidal detachment in pseudophakic eyes than phakic eyes [36% 15%, respectively, p = 0.06].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The cause was attributed to the cytokine MCP-1 (monocyte chemotactic protein-1) that increased after cataract surgery [24]. There are also some reports that there was no difference in surgical outcomes between Trab alone and Trab with simultaneous cataract surgery [25][26][27]. Regarding EXP surgery, there are some reports that surgical outcomes were not signi cantly different between Trab alone and Trab with simultaneous cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Then we compared the outcomes with the results of anti-glaucoma procedures in pseudophakic eyes. There have already been studies that include the comparison for Ex-PRESS implantation [5][6][7] and trabeculectomy [8][9][10][11][12][13][14], however they focus on these procedures separately. There is also a publication concentrating on comparing trabeculectomy combined with phacoemulsification versus Ex-PRESS implantation with phacoemulsification [15], however it proved to be inconclu-…”
Section: Introductionmentioning
confidence: 99%